Las “Exposiciones Orientalistas Salesianas” de 1943-1944: la puesta en escena de la construcción del Estado en la Amazonía ecuatoriana (Estudios) - Ortiz Batallas, Cecilia (2017)
This study scrutinizes the “Salesian Orientalist Expositions” carried out in 1943-1944 in Quito, Guayaquil and Cuenca; events that shed light on the social inclusion of Native Amazon peoples in the Ecuadorian state. The above-mentioned expositions delineated the Shuar people’s territories at a key juncture posterior to the border dispute between Ecuador and Peru of 1941. The contribution sustains that the state established itself by granting local figures the ability to conduct state affairs in this peripheral space; acts that invoked a devolution and redistribution of its powers